An efficient approach for the synthesis of 1, 2-dihydroxanthones enabled by one-pot Claisen condensation/cyclization reactions. Issue 18 (19th April 2021) - Wu, Huaimo; Liu, Song; Wang, Youyi; Yuan, Man; Zhang, Hong; Zhou, Hua; Xiao, Lianbo; Zheng, Changwu; Xu, Hongxi
Abstract : A mild, efficient method for the synthesis of 1, 2-dihydroxanthones by a one-pot reaction was developed under waste-induced relay catalysis. Abstract : 1, 2-Dihydroxanthones (DHXs) are core structures of natural products and useful building blocks in organic synthesis. So far, they have been less studied. In this report, a mild, efficient and green method for the synthesis of 1, 2-dihydroxanthones has been developed in one pot through Claisen condensation and O -cyclization under waste-induced relay catalysis with minimum organic solvents. The by-product (HMDS or NH3 ·H2 O) of the first step turned out to be the promoter for the second step, which could efficiently proceed in aqueous media without the addition of other catalysts. The reactions using trifluoroethyl salicylates could be performed under mild conditions to ensure the generation of vulnerable DHXs in high yields. The substrate scope is very broad regardless of the substituent type and its position on the structure. Specifically, the versatility of DHXs was demonstrated by their conversion to xanthones and other complex structures.